Atlantic Tropical Cyclone Strike Probabilities. Volume III. 72 Hour Movement - Crutcher,Harold L.; Quinlan,Frank T. (1971)
Probabilities relating to the future movement of North Atlantic tropical cyclones are presented. The probabilities are based on observation data of successive 12-hour positions of the centers of these storms. The data are stratified into five seasons (June-July, August, September, October, November-May) and into geographical areas defined by five-degree latitude-longitude squares. The probabilities are computed assuming the initial storm position or 'origin' is always at the center of the square and the target areas are always circular areas with radii of one, two and three degrees latitude which are also located at the center of the squares. These probabilities indicate the chance of the storm center being within the target areas at the end of specified time intervals. Two sets of probabilities are presented for each square: one set for the case when the origin is at the center of the master square, and a second set for the case where the target areas are centered on this square. Values for time intervals of 72 hours are presented in Volume III. (Author) See also Volume 2, AD-744 917. Prepared in cooperation with National Climatic Center, Asheville, N. C.